(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
A new species and a new subgenus Amphiblestrum (Aviculamphiblestrum) ruggeroi sp.n. are described from deep circalittoral-epibathyal bottoms from the Sicily Strait and the north-western Mediterranean. The new subgenus is created to distinguish, within Amphiblestrum, species with both gymnocystal adventitious and large interzooidal avicularia, both originating from basal pore chambers.